Methodological Approach to Assessing Prospects for Strategic Transformation of Retailers - M. Chorna; R. Buhrimenko; A. Zonwire (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article presents a methodological approach to assessing prospects for strategic transformation of retailers by creating free competition for fundamentally new markets, which are – the blue oceans. The approach was developed in agreement with the principles of the matrix method using modern attributes-indicators of the specific character of the activities of retailers, namely the volume of the non-food group of goods and the share of the Internet network in the structure of the retailers' turnover.